High‐resolution colonic motility recordings in vivo compared with ex vivo recordings after colectomy, in patients with slow transit constipation. Issue 12 (9th June 2016) - Dinning, P. G.; Sia, T. C.; Kumar, R.; Mohd Rosli, R.; Kyloh, M.; Wattchow, D. A.; Wiklendt, L.; Brookes, S. J. H.; Costa, M.; Spencer, N. J.
Abstract: Background: The pathogenesis of slow transit constipation (STC) remains poorly understood, with intrinsic and extrinsic abnormalities implicated. Here, we present high‐resolution colonic manometry recordings from four STC patients recorded before total colectomy, and subsequently, ex vivo, after excision. Methods: In four female, treatment‐resistant STC patients (median age 35.5 years), a fiber‐optic manometry catheter (72 sensors spaced at 1 cm intervals) was placed with the aid of a colonoscope, to the mid‐transverse colon. Colonic manometry was recorded 2 h before and after a meal. After the colectomy, ex vivo colonic manometry was recorded in an organ bath. Ex vivo recordings were also made from colons from 4 patients (2 male; median age 67.5 years) undergoing anterior resection for nonobstructive carcinoma ('control' tissue). Key Results: A large increase in 'short single propagating contractions' was recorded in STC colon ex vivo compared to in vivo ( ex vivo 61.3 ± 32.7 vs in vivo 2.5 ± 5/h). In STC patients, in vivo, the dominant frequency of contractile activity was 2–3 cycle per minute (cpm), whereas 1‐cpm short‐single propagating contractions dominated ex vivo . This same 1‐cpm frequency was also dominant in control colons ex vivo . Conclusions & Inferences: In comparison to control adults, the colon of STC patients demonstrates significantly less propagating motor activity. However, once the STC colon is excised from the body it demonstrates a regular and similar frequency of propagating activity to control tissue. This paper provides interesting insights into the control of colonic motor patterns. Abstract : Recording fibre‐optic high resolution manometry in the ex vivo and in vivo colon of patients with slow transit constipation.